The practice of military defense work on the preparation of combat reserves for the Red Army in 1941–1943 on the territory of the Khanty-Mansiysk National District - E. V. Leshukova (Омский научный вестник: Серия "Общество. История. Современность")
The article analyzes the practice of military defense work in the early years of the Great Patriotic War on the territory of the Khanty-Mansiysk National Okrug, the largest rear area in Western Siberia. The main attention is paid to the study of the activities of the Party and Soviet authorities involved in organizing activities aimed at providing the army with trained manpower reserves. The central place in this process was the organization of mass military training of the population. The study is carried out on the basis of office documentation of the Party and Soviet authorities from the State Historical Archive of the Omsk Region and the State Archive of the Socio-Political History of the Tyumen Region. Based on statistical data, the author comes to the conclusion about the significant contribution to the training of combat reserves for the Yugra front in 1941–1943. The successful military-defense work in the region was provided by the Vseobuch system and the activities of the Osoaviakhim and Red Cross organizations.